A New Perspective on the Role of Self-Confidence and Confidence in the Evaluation and Rehabilitation of Children With Adverse Life Experience and Borderline Intellectual Functioning: A Preliminary Study - Valle, Annalisa; Baglio, Gisella; Zanette, Michela; Massaro, Davide; Baglio, Francesca; Marchetti, Antonella; Blasi, Valeria (Frontiers in Psychology, 2021)
The borderline intellectual functioning (BIF) is a neurodevelopmental condition characterized by a borderline intelligence quotient (range 70–85) with difficulties in cognitive and social domains. Children with BIF often live in adverse conditions and show academic and behavioral difficulties. Rehabilitation programs for these children focus mainly on cognitive aspects, sometimes with the aid of new technologies that are able to engage and motivate. In this framework, the affective development of children with BIF and its possible role both in the difficulties they manifest and in the rehabilitation is still poorly investigated. In this work, we investigate the characteristics of the internal working models of these children by applying the separation anxiety test, using both the classical and a new coding system to identify the specific features of the attachment representation. Results delineate a profile characterized by low self-confidence and high separation anxiety, with a tendency to somatization. In the light of these results, we suggest that this attachment profile has an impact on the therapeutic relationships and on the efficacy in the use of technological devices. We propose a new perspective in which the interpersonal relationship with the psychologist and the support of the self-confidence of children are crucial to treating cognitive and behavioral difficulties in children with BIF. Only in this case, the use of new technologies and tools may be effective in promoting the greatest possible benefit from therapeutic interventions.